Automatic LHC accelerator warm-up and cool-down experience during the Long Shutdown 2. Issue 1 (1st May 2022) - Bradu, B; Brodzinski, K; Ferlin, G; Pezzetti, M; Tovar, A
Abstract: During the so-called Long Shutdown 2 (LS2), the Large Hadron Collider (LHC) has been entirely warmed-up in 2019 and cooled-down in 2020/2021 after an important maintenance period. For the first time, these complex and delicate operations have been performed in an automatic way, using a new control logic implemented in the Process Logic Controllers (PLC). This new control logic is based on similar experiences that occurred in 2008, 2013 and 2014 where many manual operations were still needed to ensure all the constraints around the machine. After a short presentation of the general LHC warm-up and cool-down principles and constraints, this paper details the global control logic that has been chosen to fulfil all requirements. This new approach is using thermodynamic considerations to spread efficiently the available helium massflows and refrigeration capacity along a LHC sector of 3.3 km (the accelerator totalizing eight cryogenic sectors), optimizing the transient time and respecting the constraints. Finally, the warm-up and cool-down achieved on the eight LHC sectors between 2019 and 2021 are presented and discussed, validating this new approach.